PERTUMBUHAN PERUSAHAAN DAN LEVERAGE : PENGARUHNYA TERHADAP PERINGKAT OBLIGASI - Marshella, Marshella; Mendari, Anastasia Sri; Soejono, Fransiska (Catholic University Musi Charitas, 2024)
This study aims to examine the effect of company growth and leverage on bond ratings by focusing on non-financial companies listed on the Indonesia Stock Exchange with a research period during 2018-2022. The data used is secondary data. The population in this study are non-financial companies listed on the Indonesia Stock Exchange. The sampling technique used was purposive sampling method and obtained 27 companies with a total of 135 observations. Hypothesis testing is done with logistic regression analysis. The growth of a company is approximated by the assets growth ratio (AGR), while leverage is approximated by the debt to equity ratio (DER). The results of this study indicate that company growth has no effect on bond ratings and leverage affects bond ratings.